Relation of genotype 22q11 deletion to phenotype of pulmonary vessels in tetralogy of Fallot and pulmonary atresia–ventricular septal defect. Issue 2 (1st February 1998) - Chessa, M; Butera, G; Bonhoeffer, P; Iserin, L; Kachaner, J; Lyonnet, S; Munnich, A; Sidi, D; Bonnet, D
Abstract : Objective: To compare the morphology of the pulmonary vessels in tetralogy of Fallot or pulmonary atresia–ventricular septal defect (PA–VSD) with (del22q) and without 22q11 deletion (non-del22q). Patients: 94 consecutive infants (54 with tetralogy of Fallot, 40 with PA–VSD) were studied using ultrasound and catheterisation. Molecular investigations: Identification of the 22q deletion was performed either by fluorescent in situ hybridisation or polymerisation chain reaction genotyping. Results: 25 patients were del22q (16/40 (40%) PA–VSD v 9/54 (17%) tetralogy of Fallot; p < 0.02). Major aortopulmonary collateral arteries was more common in patients with PA–VSD-del22q (p < 0.03). Such collaterals were identified in 13 patients: 10 del22q and three non-del22q (p < 0.001). The size of the right and left pulmonary arteries expressed as a standard deviation (SD) difference of the normal range was −4.2 (quartiles −5.3 and −2.9) for PA–VSD del22q, and −2.6 (−3.1 and −1.8) for PA–VSD non-del22q (p = 0.02). The mean (SD) difference between the measured and theoretical Nakata index was −373 (94) for PA–VSD del22q v −245 (93) in PA–VSD non-del22q (p = 0.0002). In tetralogy of Fallot patients with and without del22q, the size of the pulmonary arteries was similar (p = 0.6). Conclusions: A "specific" phenotype could be defined in patients with deletion: PA–VSD, major aortopulmonary collateral arteries with complex loop morphology, and small central pulmonary arteries. Differences in the morphology of the pulmonary vessels may indicate a different timing of the faulty developmental pathway in patients with and without 22q11 deletion.